2010
DOI: 10.1021/jp904967n
|View full text |Cite
|
Sign up to set email alerts
|

First Principles Simulation of the Bonding, Vibrational, and Electronic Properties of the Hydration Shells of the High-Spin Fe3+ Ion in Aqueous Solutions

Abstract: Results of parameter-free first principles simulations of a spin up 3d(5) Fe(3+) ion hydrated in an aqueous solution (64 waters, 30 ps, 300 K) are reported. The first hydration shell associated with the first maximum of the radial distribution function, g(FeO)(r), at d(Fe-O(I)) = 2.11-2.15 A, contains 6 waters with average d(OH) = 0.99 A, in good agreement with observations. A second shell with average coordination number 13.3 can be identified with average shell radius of d(Fe-O(II)) = 4.21-4.32 A. The waters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 92 publications
14
41
0
Order By: Relevance
“…Therefore, many-body interactions, including polarization, are included in a parameter free way as the simulation proceeds. For highly charged ions, it has been demonstrated that AIMD works reliably [12][13][14]21 and we will show that there is very good agreement between simulated extended x-ray absorption fine structure ͑EXAFS͒ spectra and the results of measurements.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Therefore, many-body interactions, including polarization, are included in a parameter free way as the simulation proceeds. For highly charged ions, it has been demonstrated that AIMD works reliably [12][13][14]21 and we will show that there is very good agreement between simulated extended x-ray absorption fine structure ͑EXAFS͒ spectra and the results of measurements.…”
Section: Introductionsupporting
confidence: 56%
“…21͒ and Fe 3+ . 14 However, in contrast to Al 3+ , the structure of this shell is not completely trigonal. As shown in Fig.…”
Section: A the Hydration Shell Structurementioning
confidence: 92%
See 1 more Smart Citation
“…13,17,18 The experimental result for the CN of the second hydration shell is ~12. 7 Our simulated CN of the second shell is ~14, close to those (13.3 -13.6) obtained from quantum mechanical / first principle simulations.…”
Section: A) Applicability Of Ferric Ion Potentials Designed For Solimentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] Efforts have been made to correctly reproduce the experimentally derived structure of the hydration shells around an iron cation using molecular dynamics (MD) simulations 9,10,14,15,19,20 , first principle calculations 11,18 and ab initio molecular dynamics simulations 13,17,18,20 . Density functional theory (DFT) also has been used to study the structure, energetics and electronic properties of iron-water/hydroxyl 4 molecular species in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%